Redefining postoperative hypertension management in carotid surgery: a comprehensive analysis of blood pressure homeostasis and hyperperfusion syndrome in unilateral vs. bilateral carotid surgeries and implications for clinical practice - Sultan, Sherif; Acharya, Yogesh; Dulai, Makinder; Tawfick, Wael; Hynes, Niamh; Wijns, William; Soliman, Osama (Frontiers in Surgery, 2024)
This study evaluates the implications of blood pressure homeostasis in bilateral versus unilateral carotid surgeries, focusing on the incidence of postoperative hypertension, hyperperfusion syndrome, and stroke as primary outcomes. It further delves into the secondary outcomes encompassing major adverse cardiovascular events and all-cause mortality.Spanning two decades , this comprehensive retrospective research encompasses 15,369 carotid referrals, out of which 1,230 underwent carotid interventions. A subset of 690 patients received open carotid procedures, with a 10-year follow-up, comprising 599 unilateral and 91 bilateral surgeries. The Society for Vascular Surgery Carotid Reporting Standards underpin our methodological approach for data collection. Both univariate and multivariate analyses were utilized to identify factors associated with postoperative hypertension using the Statistical Package for the Social Sciences (SPSS) Version 22 (SPSS®, IBM® Corp., Armonk, N.Y., USA).A marked acute elevation in blood pressure was observed in patients undergoing both unilateral and bilateral carotid surgeries (p<0.001). Smoking (OR: 1.183, p=0.007), hyperfibrinogenemia (OR: 0.834, p=0.004), emergency admission (OR: 1.192, p=0.005), severe ipsilateral carotid stenosis (OR: 1.501, p=0.022), and prior ipsilateral interventions (OR: 1.722, p=0.003) emerged as significant factors that correlates with postoperative hypertension in unilateral surgeries.Conversely, in bilateral procedures, gender, emergency admissions (p=0.012), and plaque 4 morphology (p=0.035) significantly influenced postoperative hypertension. Notably, 2.2 % of bilateral surgery patients developed hyperperfusion syndrome, culminating in hemorrhagic stroke within 30 days. Intriguingly, postoperative stage II hypertension was identified as an independent predictor of neurological deficits post-secondary procedure in bilateral CEA cases (p=0.004), attributable to hyperperfusion syndrome. However, it did not independently predict myocardial infarction or mortality outcomes. The overall 30-day stroke rate stood at 0.90%. Lowest incidence of post operative hypertension or any complications were observed in eversion carotid endartrertomy.The study identifies postoperative hypertension as a crucial independent predictor of perioperative stroke following bilateral carotid surgery. Moreover, the study elucidates the significant impact of bilateral CEA on the development of post-operative hyperperfusion syndrome or stroke, as compared to unilateral CEA. Currently almost 90% of our carotid practice is eversion carotid endartrerectomy.